Persistent Parasitemia Despite Dramatic Reduction in Malaria Incidence After 3 Rounds of Indoor Residual Spraying in Tororo, Uganda. (1st November 2018) - Nankabirwa, Joaniter I; Briggs, Jessica; Rek, John; Arinaitwe, Emmanuel; Nayebare, Patience; Katrak, Shereen; Staedke, Sarah G; Rosenthal, Philip J; Rodriguez-Barraquer, Isabel; Kamya, Moses R; Dorsey, Grant; Greenhouse, Bryan
Abstract: Background: Indoor residual spraying of insecticide (IRS) has been associated with reductions in the incidence of malaria, but its impact on malaria parasitemia is unclear. Methods: We followed 469 participants from August 2011 to May 2016 in Tororo, Uganda, a historically high malaria transmission setting. Three rounds of IRS with bendiocarb were implemented from December 2014 to December 2015. Symptomatic malaria episodes were identified by passive surveillance. Parasitemia was identified by active surveillance every 1–3 months using microscopy and Plasmodium falciparum –specific loop-mediated isothermal amplification. Results: IRS was associated with a significant decline in the incidence of symptomatic malaria irrespective of age (episodes per person per year declined from 3.98 to 0.13 in children aged <5 years, 2.30 to 0.15 in children aged 5–10 years, and 0.41 to 0 in adults; P < .001 for all). IRS significantly reduced the prevalence of parasitemia, but the prevalence remained high (pre-IRS to post–third round: 58.5% to 11.3% in children aged <5 years, 73.3% to 23.7% in children aged 5–10 years, and 52.2% to 15.4% in adults; P < .001 for all). Conclusions: Although IRS was associated with significant reductions in the incidence of malaria and prevalence of parasitemia, a proportion of the population remained parasitemic, providing a potential reservoir for malaria transmission. Abstract : Three rounds of indoor residual spraying were associated with significant reduction in clinical malaria and parasite prevalence; however, a proportion of the proportion remained parasitemic. These parasites could serve as a reservoir for onward transmission.